Determinants of Fifth-Party Logistics (5PL): Service providers for Supply Chain Management - Hosie, Peter; Bulan, S.; Tan, A.; Kozlak, A. (Inderscience Publishers, 2012)
The theory and practice of a networked approach to Supply Chain Management (SCM) are used to trace the evolution of management logistics. Reforming influences on competitive forces have deregulated, globalised and innovated, changing fundamentally the conception and practice of SCM. Increased need for strong interfirm networks, among other trends, seems formative. Changed purchasing and customer service functions result in new management methods, business contexts and transportation modes. Radical advances in managing supply chains stem from electronic commerce, notably in transportation and distribution, now widely adopted. Hence, managing logistics services becomes basic to businesses' competitiveness. Economic imperatives, technological innovations, market competition and managerial ability to provide advanced logistics services is encouraging increased trust between firms and their SCM providers. Issues and future trends are prompting the outsourcing of Fourth Party Logistics (4PL) services are identified. Possible future '5PL' services are meta-analytically indicated, with future empirical research suggestions based on novel insights.